The Concept Of Virginity From the Perspective of Islam And Muslim Women - Siti Nazla Raihana; Salma Nuha Ghufron (An-Nisa' Journal of Gender Studies, 2023)
This research delves into the intricate interplay between societal norms and the honor attributed to women, specifically addressing the pervasive myths surrounding the virginity of Muslim women in Indonesia. Rooted in the negative impacts experienced by women due to their virginity status, this inquiry seeks to unravel the perspectives of 17 Muslim women on the significance of virginity within the context of Islamic teachings. Employing qualitative research methods, including in-depth interviews, the study illuminates nuanced dimensions, shedding light on how these women navigate the complexities surrounding their virginity. The findings underscore three pivotal conclusions: Indonesian Muslim women emphasize the importance of virginity and the need to protect it. Importantly, they highlight that virginity is not solely judged based on the hymen. Moreover, their stories reveal that Islam honors women who maintain their virginity. These conclusions contribute significantly to a more comprehensive understanding of the societal implications and individual experiences associated with the concept of virginity among Muslim women in Indonesia. The study's outcomes hold the potential to inform broader discussions on cultural perceptions and foster awareness, promoting respectful discourse surrounding the role of virginity within the social fabric.